Fish diversity and assemblage in the Batticaloa lagoon, Sri Lanka. Issue 4 (1st February 2023) - Harris, Jalaldeen Mohamed; Vinobaba, Periyathamby; Kularatne, Ranil Kavindra Asela; Khan, Syed Ajmal
Abstract: The Batticaloa Lagoon (Sri Lanka's third‐largest brackish waterbody) has suffered habitat degradation and water quality deterioration during the past 30 years due to various anthropogenic activities. Despite Sri Lanka having 40 lagoons, inventories on the lagoon ichthyofauna are rather meagre and data on fish diversity and assemblages are scarce. An assessment of fish diversity is essential to maintain the ecological stability and lagoon fisheries. This study examined the fish fauna of the Batticaloa lagoon considering the northern and southern regions of the lagoon and various depths through a 3‐year survey (2017–2019) and documented the dominant and rare fish species. In addition, biodiversity measures, species assemblages and the role of environmental parameters on the distribution of fishes were documented. Various diversity indices (the Margalef richness index, the Shannon–Weiner diversity index, Pielou's evenness index, the dominance index, the taxonomic diversity index, the average taxonomic distinctness index and the total taxonomic distinctness index) were calculated. Analysis of similarities (ANOSIM) was used to examine the seasonal and regional differences in the fish assemblages. The survey showed the occurrence of 96 species belonging to 40 families and 11 orders. Ambassis gymnocephalus was the most abundant fish species (8.7% of the total number of fishes collected) followed by Etroplus suratensis (6.8%), Arius maculatus (6.1%), Gerres filamentosus (5.3%), Oreochromis niloticus (4.6%) and Gerres abbreviates (3.9%). Dasyatis uarnak (0.02%), Acanthurus gahhm (0.03%), Alectis ciliaris (0.04%) and Crossorhombus valderostratus (0.08%) were considered as rare species which constitute less than 0.1% of the total while D. uarnak was considered a doubletons species (represented twice in the whole sample of 16 stations). Two types of species assemblages, one in the northern region and one in the southern region, were evident in a dendrogram (Based on the samples were collected on each region dendrogram were plotted with respect to sites then finally dendrogram of one region pratly connected by other region) based on sample composition similarity estimated with a Bray–Curtis matrix and nonmetric multidimensional scaling plots. The Bray–Curtis dissimilarity was 59.03% between the two regions, indicating statistically significant differences in assemblages (ANOSIM R 0.801; P  < 0.01). The northern region of the lagoon had a higher number of species, density, Margalef richness, Pielou's evenness, Shannon–Wiener diversity, taxonomic diversity, taxonomic distinctness and total taxonomic distinctness compared to the southern region. The northern region showed significantly higher levels of salinity and dissolved oxygen (DO) and the southern region higher temperature, turbidity, phosphates and nitrates. The best subset of biota and environmental variables [BEST(BIO‐ENV)] test showed a significant relationship between fish assemblage and environmental parameters. Distance‐based linear model analysis showed a significant relationship between fish assemblage and the environmental parameters salinity, temperature, pH and DO. The sequential test of this analysis showed the environmental parameters to explain about 74.9% ( R 2 ) of the total variation. The bioenvironmental model developed was found to be appropriate. Thirteen species were found to be influential as they explained the overall fish distribution pattern with a Spearman rank correlation of 0.951. Ten groups of coherent species were also identified in the study area. In stations having anthropogenic activities, the fish diversity was low. The fish fauna of the Batticaloa lagoon should be monitored periodically to protect the fishery resources here. An understanding of the role that environment plays in structuring the fish assemblage in the Batticaloa lagoon and locations with critical habitats will be of great importance in the conservation and management of fishery resources in this lagoon. However, as monitoring only the dominant species may fail to pick up on important impacts affecting the less common species, it should be done using diversity indices and rare fish species. Monitoring is imperative in view of the livelihood of the fishers this lagoon supports and the health of the local people, as fish is a healthy food. The fishery resources of this lagoon must be protected for posterity with appropriate management measures.